Removal of ECG Baseline Wander using Savitzky-Golay Filter Based Method - Nahiyan, KM Talha; Amin, Abdullah Al (Bangladesh Journal of Medical Physics, 2017)
ECG (Electrocardiogram) is a measure of hearts electrical activity. As the body is a volume conductor, ECG signal can be recorded from the body surface. The signal while being recorded from the body surface gets corrupted by various types of noise or artifact. Among these, baseline wander is a type of noise that severely hampers the ECG signal. Baseline wander is particularly of very low frequency; it causes the ECG signal to deviate from its isoelectric line and causes the signal to ride on the lower frequency artifact. The proposed method is based on Savitzky-Golay filter, which is a moving average filter that takes into consideration the polynomial order along with moving averaging when approximating the signal. It enables to approximate the baseline wander quite efficiently. Though in some cases it distorts the ECG signal to some extent, when compared with usual polynomial fitting method, it demonstrates superiority in terms of accuracy, simplicity and generalization. Bangladesh Journal of Medical Physics Vol.8 No.1 2015 32-45